Dendroglaciological Dating of a Little Ice Age Glacial Advance at Moving Glacier, Vancouver Island, British Columbia - Smith, Daniel; Laroque, Colin (Géographie physique et Quaternaire, 1996)
ABSTRACTDendrochronological investigations at Moving Glacier provide the first calendar-dating of a Little Ice Age glacier advance on Vancouver Island. In 1931, Moving Glacier was within 30 to 50 m of a distinct trimline and terminal moraine marking its maximum Little Ice Age extent. A reconnaissance of the site in 1993 revealed the presence of sheared in situ stumps and detrital trunks inside the 1931 ice limit. Sampling in 1994 showed the site was covered by a mature subalpine forest prior to the glacial advance which overrode the site after 1718 A.D. Following this period of expansion, which saw Moving Glacier expand to its maximum Little Ice Age position after 1818 A.D., the glacier apparently experienced only minimal retreat prior to first being photographed in 1931.